2019
DOI: 10.1007/s12253-019-00734-w
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and Dopamine Receptor Expression in Solid Tumours Including Rare Cancers

Abstract: In preclinical studies serotonin stimulates and dopamine inhibits tumour growth and angiogenesis. Information regarding serotonin and dopamine receptor (5-HTR and DRD) expression in human cancers is limited. Therefore, we screened a large tumour set for receptor mRNA overexpression using functional genomic mRNA (FGmRNA) profiling, and we analysed protein expression and location of 5-HTR1B, 5-HTR2B, DRD1, and DRD2 with immunohistochemistry in different tumour types. With FGmRNA profiling 11,756 samples represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Existing studies had shown that HTR1B indeed had close relationship with malignant tumor.A stduy result demonstrated that 5-HTR1B, 5-HTR2B, DRD1, and DRD2 showed mRNA overexpression in a broad spectrum of common and rare cancers. 13 To obtain the recurrence risk model that identifies patients at low and high risk for recurrence, a other study was constructed, followed by the validation of its performance in the validation set and a microarray dataset. Totally, 378 differentially expressed genes(DEGs), including 20 recurrence-associated DEGs were identified between the recurrent and non-recurrent tumors in the training set.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies had shown that HTR1B indeed had close relationship with malignant tumor.A stduy result demonstrated that 5-HTR1B, 5-HTR2B, DRD1, and DRD2 showed mRNA overexpression in a broad spectrum of common and rare cancers. 13 To obtain the recurrence risk model that identifies patients at low and high risk for recurrence, a other study was constructed, followed by the validation of its performance in the validation set and a microarray dataset. Totally, 378 differentially expressed genes(DEGs), including 20 recurrence-associated DEGs were identified between the recurrent and non-recurrent tumors in the training set.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was discovered that there are many kinds of 5-HTR subtypes on a variety of cancers, including PC (32), HCC (3335), CRC (36) etc. 5-HT could promote the development and progression of these cancers by activating the 5-HTR subtypes, such as 5-HT1A, 5-HT1B, 5-HT2A, 5-HT2B (44, 99). 5-HT1B was overexpressed in human NPC samples (44), which reminded us that the elevated 5-HT in plasma in NPC could promote the progression of NPC through 5-HTR.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT could promote the development and progression of these cancers by activating the 5-HTR subtypes, such as 5-HT1A, 5-HT1B, 5-HT2A, 5-HT2B (44, 99). 5-HT1B was overexpressed in human NPC samples (44), which reminded us that the elevated 5-HT in plasma in NPC could promote the progression of NPC through 5-HTR. These findings suggest that the significantly elevated C. ramosum in the intestinal flora of NPC patients may affect the development and progression of NPC through increasing the 5-HT levels in the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another hypothesis is that serotonin’s mitogenic effect is dose-dependent, where higher doses promote cell proliferation and lower doses cause vasoconstriction on tumor vessels, leading to inhibition of tumor growth. By contrast, several genetic studies have shown a decreased 5-hydroxytryptamine receptor 1B gene (HTR1B) in the lung, renal, osteosarcoma, and non-Hodgkin’s lymphoma, suggesting that serotonin may behave as a tumor suppressor when it interacts with 5-HTB receptor subtypes [ 49 ].…”
Section: Serotonin Pathway As a Potential Therapeutic Targetmentioning
confidence: 99%